2023
DOI: 10.1590/0034-7167-2022-0677
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the components of sarcopenia and quality of life perceived of individuals on hemodialysis

Bianca Raquel Bianchi Celoto,
Flávia Andréia Marin,
Maria Claudia Bernardes Spexoto

Abstract: Objectives: to evaluate the prevalence of sarcopenia in individuals aged 50 years or older on hemodialysis; to verify the association between sarcopenia and sociodemographic, clinical, anthropometric factors, components of sarcopenia and quality of life (QoL); and to correlate the components of sarcopenia with QoL. Methods: Participated 83 individuals on hemodialysis. Sarcopenia was established according to the current European consensus. Dynamometry to determine strength, calf circumference (CC) and appendic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…This is supported by the results of recent studies that found an association of HRQoL and sarcopenia in patients with heart failure and patients with colorectal cancer [ 45 , 68 ]. Another recent study by Celoto et al could not find a correlation between HRQoL and muscle mass in patients undergoing hemodialysis, which seems plausible as this condition differs vastly from cancer [ 69 ]. A study in patients with liver cell cancer, however, also found a correlation between sarcopenia and HRQoL in a prospective study [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the results of recent studies that found an association of HRQoL and sarcopenia in patients with heart failure and patients with colorectal cancer [ 45 , 68 ]. Another recent study by Celoto et al could not find a correlation between HRQoL and muscle mass in patients undergoing hemodialysis, which seems plausible as this condition differs vastly from cancer [ 69 ]. A study in patients with liver cell cancer, however, also found a correlation between sarcopenia and HRQoL in a prospective study [ 70 ].…”
Section: Discussionmentioning
confidence: 99%